Psicologias e transexualidades: o estado da arte da produção teórica brasileira - Pacheco, Bárbara Guimarães Costa (2017)
This dissertation analyzed published publications in the interface between psychology and transsexuality, in order to identify the discourses about the transsexualities that circulated and impacted scientific production of Brazilian psychology in the period from 1997 to 2015. For this purpose, a Literature Review Systematized Descriptive in virtual databases was per-formed: Bank of Higher Education Personnel Improvement Coordination Thesis (CAPES), Brazilian Digital Library of Theses and Dissertations (BDTD), Scielo, Pepsic and IndexPsi. It were searched the terms "transsexual", "transsexuals", "gender identity clinic", "transgender", which were used independently and only in Portuguese. In order to complement this search, a survey of research groups registered in the National Council for Scientific and Technological Development (CNPq) was carried out, which presented, among its lines of research, the pro-duction of knowledge about gender and sexuality, and a E-mail contact was made with their leaders requesting information about publications and / or works defended by members of the group and / or others and that fit into this theme. A total of 729 papers were identified, in-cluding theses, dissertations and scientific papers. Of these, 648 were excluded and 81 were selected for analysis, being 12 theses, 31 dissertations and 38 scientific articles. In order to analyze the included productions, content analysis procedures were used, intending to respond to the proposed objectives. From the reading of the work in its entirety, as well as the dia-logue with the document entitled "Guidelines for psychological practice with transgender and gender nonconforming people" elaborated by the APA, it was possible to construct the cate-gories: evaluation, therapy and intervention; Foundational knowledge and awareness; Stigma, discrimination and barriers to care. In general, the results point to the recent inclusion of this theme in the field of psychology, as well as its linkage to academic spaces. This is an im-portant element to (re) think the relationship between LGBT activists and researchers, because if this is the space for legitimizing normative practices, it has also been the space of subver-sion and production of other psychologies. Likewise, the nodal point of the discussions in the identified papers seems to be organized in the diagnosis of transsexuality: although recent works defend the diagnosis should be made in the perspective of identifying "a true transsex-ual", they are minority in this field. The refusal to diagnosis seems to forge a consensus, how-ever, this only occurs when it refers to the specific point of the manifestation of the desire of the surgery as a diagnostic criterion and the diagnosis as a gateway to the service. However, the same alignment or criticism is not observed in relation to the compulsory treatment and the minimum time of care, also provided for by the Resolution of the Federal Medical Council (CFM) and incorporated into the Transitional Procedural Ordinance. In addition, few works have untied the transsexualities of the health field and the limits of diagnosis. However, these are the works that seem to have a greater commitment to the perspective of the depathologiza-tion of transsexualities as they contribute their looks in the struggles for visibility and other spheres of sociability for the transsexual people.